2005
DOI: 10.2139/ssrn.840264
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Surplus in Online Auctions

Abstract: Despite the growing research interest in Internet auctions, particularly those on eBay, little is known about quantifiable consumer surplus levels in such mechanisms. Using an ongoing novel field experiment that involves real bidders participating in real auctions, and voting with real dollars, we collect and examine a unique dataset to empirically quantify and understand determinants of consumer surplus in eBay auctions. The estimation procedure for private value auctions relies mainly on knowing the highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 46 publications
3
57
0
Order By: Relevance
“…Our analysis reveals that consumer surplus is enhanced by as much as $97.92 million per year because of the availability of the electronic market. This finding thus contributes to the literature on the welfare benefits of the Internet (Brynjolfsson et al 2003, Ghose et al 2006, Bapna et al 2008, Forman et al 2009). Consistent with an emerging stream of work (Granados et al 2009), we find that online markets exhibit higher own price elasticity, compared to that of offline markets.…”
Section: Introductionsupporting
confidence: 67%
“…Our analysis reveals that consumer surplus is enhanced by as much as $97.92 million per year because of the availability of the electronic market. This finding thus contributes to the literature on the welfare benefits of the Internet (Brynjolfsson et al 2003, Ghose et al 2006, Bapna et al 2008, Forman et al 2009). Consistent with an emerging stream of work (Granados et al 2009), we find that online markets exhibit higher own price elasticity, compared to that of offline markets.…”
Section: Introductionsupporting
confidence: 67%
“…This technique has been applied to measure welfare gains for new goods ranging from Honeynut Cheerios (Hausman 1997b) to increased product variety on the Internet (Brynjolfsson et al 2003). Related techniques have also been used to analyze the welfare impact from online auction sites (Bapna et al 2005).…”
Section: Literaturementioning
confidence: 99%
“…Research has found that product specialization has explanatory power for reverse auctions. However, research has also found that non-contractible elements (including non-contractibility quality, supplier technological investments, information exchange, information diffusion, responsiveness, trust, and flexibility, of inter-organizational relationships) also have great explanatory power for reverse auctions (Ba, Whinston, & Zhang, 2003;Bapna, Jank, & Shmueli, 2008;Ho, Bodoff, & Tam, 2011;Li, Hess, & Valacich, 2006Lim, Sia, Lee, & Benbasat, 2006;Mithas, Jones, & Mitchell, 2008;Webster & Martocchio, 1992). Research has also found implementing information feedback to an auction system to increase the amount of successful trading on the auction websites because it helps build trust, which is critical in electronic auctions (Adomavicius, Curley, Gupta, & Sanyal, 2013;Adomavicius & Gupta, 2005;Ba et al, 2003;Bapna et al, 2003).…”
Section: Electronic Auctions and Bidding Behaviormentioning
confidence: 99%